RETORIKA DHARMA WACANA PADA ANAK BERKELAINAN PENDENGARAN (TUNA RUNGGU) DI SLB MATARAM - Ni Nyoman Harnika; Ketut Yuniati (Maha Widya Duta : Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2022)
Communication about Hindu religious teachings are need everyone without _ except child different . Child worthy have different types , wrong _ the only one is child different hearing ( deaf ). Implementation communication to child deaf could conducted with carry out the dharma of discourse , however implementation different implementation of discourse dharma on usually . Problem in study this is how retorika dharma discourse on child different hearing ( deaf ) at SLB Mataram City . Method study in study this is use method qualitative descriptive that is describe retorica dharna discourse on child different hearing ( deaf ). Results study this is retorica pendharna discourse is communicate Hindu religious teachings with two type communication that is verbal and nonverbal communication and tucked in a little humorKeywords : Retorika, discourse dharma, deaf